Research on the drive of a plant for the preparation and transportation of building mortars - Chyslo, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2025)
Modern mixing plants for the preparation of mortar and concrete mixtures are an important component of construction technologies, which leads to increased requirements for their energy efficiency, operational reliability and stability of operation under conditions of variable loads. At the stage of designing the drive of the mixing plant, a well-founded determination of the power of the electric motor, gear ratios and kinematic parameters of the drive system requires special attention. The article examines the theoretical study of the drive of a compact installation for the preparation and pipeline transportation of construction mortars, the key design feature of which is the use of a single electric motor for driving a forced-action blade mixer and a piston solution pump through a common gear reducer and chain transmission. The kinematic scheme of the drive was analyzed taking into account the moments of inertia of the main elements of the system, dynamic models for estimating torsional oscillations were presented. The nature of variable moments of resistance caused by cyclic load from working bodies is considered. It was established that the dynamic loads that occur during the engagement of gears, starting and braking modes, as well as due to the unevenness of the resistance forces, significantly affect the fatigue strength and durability of the gearbox. The obtained results make it possible to substantiate the rational parameters of the drive, to propose measures to reduce peak loads and to increase the energy efficiency and reliability of small-sized installations for construction sites.